Does labour social responsibility disclosure affect financial performance? Evidence from Indonesia - Esa Anesti Putri Muhardini; Iman Harymawan; Mohammad Nasih; Akmalia Mohamad Ariff (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This study examines the effect of disclosure of labour social responsibility on the company's financial performance as measured by operational aspects (ROA), profitability aspects (ROE), and sales aspects (ROS). This study uses regression analysis to examine the relationship between labour social responsibility disclosure and financial performance of companies listed on the Indonesia Stock Exchange during 2015-2020 and indexed by GRI. The results of this study indicate that the disclosure of employment social responsibility has a significant effect on the achievement of financial performance aspects of operations (ROA) and financial performance aspects of sales (ROS), while if it is associated with the achievement of financial performance aspects of profitability (ROE), there is no significant effect on employee social responsibility disclosure. This research contributes to achieving sustainable development goals by providing views for companies regarding the impact of implementing and disclosing employment social responsibilities and contributing to literature related to labour, financial performance, and sustainability disclosure. This novel research provides groundbreaking insights into the impact of implementing and disclosing employment social responsibilities on financial performance, highlighting the importance of labor, financial performance, and sustainability disclosure in achieving sustainable development goals.